# |
ODE |
Mathematica |
Maple |
\[
{}-a y^{3}-\frac {b}{x^{{3}/{2}}}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}a x y^{3}+b y^{2}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x^{a} y^{3}+3 y^{2}-x^{-a} y-x^{-2 a}+a \,x^{-a -1} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\left (y-f \left (x \right )\right ) \left (y-g \left (x \right )\right ) \left (y-\frac {f \left (x \right ) a +b g \left (x \right )}{a +b}\right ) h \left (x \right )-\frac {f^{\prime }\left (x \right ) \left (y-g \left (x \right )\right )}{f \left (x \right )-g \left (x \right )}-\frac {g^{\prime }\left (x \right ) \left (y-f \left (x \right )\right )}{g \left (x \right )-f \left (x \right )} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y^{3}+y^{2} a = 0
\] |
✓ |
✓ |
|
\[
{}\left (a x +b \right )^{2} y^{\prime }+\left (a x +b \right ) y^{3}+c y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (-x^{2}+1\right )+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{a x}+a y
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y+\left (1-y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a y^{2} x
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y^{2}+\left (x^{2}-x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y \left (x^{2}+1\right ) y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}\frac {x}{1+y} = \frac {y y^{\prime }}{1+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2} b^{2} = a^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (y\right ) = \cos \left (x \right ) \sin \left (y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}a x y^{\prime }+2 y = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2}+y^{\prime } = \frac {a^{2}}{x^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = y \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }-x y = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y^{2}+x}{x^{2} y-y}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x y^{2}-8 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+y\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = x
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } = 3 \left (y-2\right )^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}\left (x +x y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+3 x y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y-x \,{\mathrm e}^{-x^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = 2 x^{{5}/{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y = \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {x^{2}+1}} = \frac {1}{x +\sqrt {x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}\left (1+{\mathrm e}^{x}\right ) y^{\prime }+2 y \,{\mathrm e}^{x} = \left (1+{\mathrm e}^{x}\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } x \ln \left (x \right )+y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime } = x y+2 x \sqrt {-x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tanh \left (x \right ) = 2 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \cos \left (y \right )-x \tan \left (y \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x-{\mathrm e}^{y} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {3 y^{{2}/{3}}-x}{3 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = x y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = 2 x^{{3}/{2}} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x +3 y^{3} = 1
\] |
✓ |
✓ |
|
\[
{}2 x \,{\mathrm e}^{3 y}+{\mathrm e}^{x}+\left (3 x^{2} {\mathrm e}^{3 y}-y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) y^{\prime }+x +y+1 = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )+\sin \left (x \right )^{2}-\left (\sin \left (x \right ) \sin \left (y\right )+\cos \left (y\right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y^{2}-x y = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = -x +\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y+\left (y^{2}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x y+\left (x y+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}-\tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime }+y-\frac {1}{x^{2}}+\frac {2}{x^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{2}-\frac {2 y}{x}-\frac {1}{x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{2}}{x}+\frac {y}{x}-2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-x} y^{2}+y-{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-x y = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}x \ln \left (y\right ) y^{\prime }-y \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x -y \sin \left (2 x \right ) = \left (\sin \left (x \right )^{2}-2 y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}3 x^{3} y^{2} y^{\prime }-x^{2} y^{3} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y-y^{2} {\mathrm e}^{3 x} = 0
\] |
✓ |
✓ |
|
\[
{}u \left (-v +1\right )+v^{2} \left (1-u\right ) u^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 x -x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y+2 x \right ) y^{\prime }-x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (y\right )-{\mathrm e}^{-\sin \left (y\right )}\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )^{2} y^{\prime }+\sin \left (x \right )^{2}+\left (x +y\right ) \sin \left (2 x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}\sin \left (\theta \right ) \cos \left (\theta \right ) r^{\prime }-\sin \left (\theta \right )^{2} = r \cos \left (\theta \right )^{2}
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y+x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x y+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\sin \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y^{2}-3 y+1
\] |
✓ |
✓ |
|
\[
{}s^{\prime } = t \ln \left (s^{2 t}\right )+8 t^{2}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = \frac {y \,{\mathrm e}^{x +y}}{x^{2}+2}
\] |
✓ |
✓ |
|
\[
{}\left (x y^{2}+3 y^{2}\right ) y^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}s^{2}+s^{\prime } = \frac {s+1}{s t}
\] |
✗ |
✗ |
|
\[
{}x y^{\prime } = \frac {1}{y^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 3 x t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {t \,{\mathrm e}^{-t -2 x}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y^{2} \sqrt {1+x}}
\] |
✓ |
✓ |
|
\[
{}x v^{\prime } = \frac {1-4 v^{2}}{3 v}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sec \left (y\right )^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} \left (1+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-x^{3} = x
\] |
✓ |
✓ |
|
\[
{}x +x y^{2}+{\mathrm e}^{x^{2}} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{y}+y \,{\mathrm e}^{\cos \left (x \right )} \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2}\right ) \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{3} \left (1-y\right )
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{2} = \sqrt {1+y}\, \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = \frac {4 x^{2}-x -2}{\left (1+x \right ) \left (1+y\right )}
\] |
✓ |
✓ |
|